2019
DOI: 10.1016/j.whi.2019.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Pain Intensity and Pain Interference in Male and Female Iraq/Afghanistan-era Veterans

Abstract: Background: Chronic pain conditions are common among both male and female Iraq/Afghanistan-era veterans and can have substantial negative impacts on quality of life and function. Although in general women tend to report higher levels of pain intensity than men, findings remain mixed on whether gender differences in pain exist in Iraq/ Afghanistan-era veterans. Additionally, the relationships between functional impairment, pain intensity, and gender remain unknown. Methods: This project examined gender differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 54 publications
(72 reference statements)
0
14
3
Order By: Relevance
“…The included works stem from not only trials (Danan, Sherman, et al, 2019a) and cohort studies (Dursa et al, 2019;Harrington et al, 2019;Naylor et al, 2019;Brown et al, 2019), but also clinical program evaluations (Kumpula et al, 2019), VA patient experience surveys (Breland et al, 2019), and research process metrics (Goldstein et al, 2019). Multiple VA research entities are represented in this collection, including the Cooperative Studies Program (e.g., Harrington et al, 2019;Brown et al, 2019), the VA Evidence Synthesis Program (Danan, Ullman, et al, 2019b), Health Services Research & Development (Combellick et al, 2019;Danan, Sherman, et al, 2019a;Goldstein et al, 2019), and Mental Illness Research Education Clinical Centers of Excellence (Naylor et al, 2019). Bovin et al exemplify the usefulness of combining the VA's array of data sources, including electronic medical record and research survey data, to produce clinically important findings related to MST screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The included works stem from not only trials (Danan, Sherman, et al, 2019a) and cohort studies (Dursa et al, 2019;Harrington et al, 2019;Naylor et al, 2019;Brown et al, 2019), but also clinical program evaluations (Kumpula et al, 2019), VA patient experience surveys (Breland et al, 2019), and research process metrics (Goldstein et al, 2019). Multiple VA research entities are represented in this collection, including the Cooperative Studies Program (e.g., Harrington et al, 2019;Brown et al, 2019), the VA Evidence Synthesis Program (Danan, Ullman, et al, 2019b), Health Services Research & Development (Combellick et al, 2019;Danan, Sherman, et al, 2019a;Goldstein et al, 2019), and Mental Illness Research Education Clinical Centers of Excellence (Naylor et al, 2019). Bovin et al exemplify the usefulness of combining the VA's array of data sources, including electronic medical record and research survey data, to produce clinically important findings related to MST screening.…”
Section: Discussionmentioning
confidence: 99%
“…Negative findings are informative for identifying when gender-specific services may not be needed. Second, Naylor et al (2019) examined the experience of pain among Operation Iraqi Freedom/Operation Enduring Freedom/ Operation New Dawn veterans. They found that women reported higher levels of pain than men, and that pain intensity explained gender differences in pain interference.…”
Section: Health Conditions and Health Behaviorsmentioning
confidence: 99%
“…Although it is risky to act on findings from exploratory subgroup analyses, based on interaction tests, they can be used, if interpreted cautiously, to generate hypotheses that are tested in future studies (see Brown et al, [2019] and Danan et al, [2019]). Furthermore, the risks of producing type 1 errors (false positives) can be mitigated by correcting for multiple comparisons (see Benjamini & Hochberg [1995] and Naylor et al, [2019]). Although stratified analyses are not good indicators of whether sex or gender differences exist, if all studies routinely presented findings stratified by sex or gender, perhaps as supplementary materials with warnings about overinterpretation of findings, power issues could be addressed through meta-analysis techniques (Wizeman, 2012).…”
Section: Research Designs and Statistical Techniques That Can Illuminmentioning
confidence: 99%
“…Thus, it is not surprising that pain and mental illnesses are commonly comorbid for Veterans [ 13 ]. Research suggests that pain is strongly associated with symptoms of anxiety, depressive disorders, suicidal ideation, and PTSD [ 13 – 15 ]. Poundja et al [ 16 ] found that both pain severity and pain interference are negatively correlated with mental health quality of life in Canadian veterans suffering from traumatic stress.…”
mentioning
confidence: 99%